Ramadan for everyone : a Muslim community story - Khalil, Aya (Little, Brown and Company, 2025)
"Celebrate the holy month of Ramadan with this luminous picture book about faith, community, sisterhood, and acts of service. Ramadan is here! And this year, Habeeba is finally going to fast all day, every day, and pray all the special Ramadan prayers at night at the masjid, just like her older sister, Sumaya. The holy month is filled with decorations, beading, crafts, delicious recipes, religious ceremonies--so much activity that it's hard for Habeeba to stay awake during prayer services or to resist Baba's gooey, cheese-filled kunafa drenched in sweet syrup when she gets home from school. Habeeba is discouraged. How else can she be observant like Sumaya?"--